The Influence of Work Conflict and Work Discipline on the Work Performance of ASN at the Regional Disaster Management Agency of Sijunjung Regency - Lenny Hasan; Henny Sjafitri (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to determine and analyze how much influence work conflict has on the work performance of ASN in the Regional Disaster Management Agency of Sijunjung Regency partially and simultaneously. The research method used is a quantitative method, the type of quantitative method is descriptive quantitative. The sample determination is determined by saturated sampling technique where all populations are sampled as many as 39 people. The analysis technique used is multiple linear regression analysis. Based on the t test conducted, work conflict partially has a significant effect on the work performance of ASN in the Regional Disaster Management Agency of Sijunjung Regency and work discipline partially has a significant effect on the work performance of ASN in the Regional Disaster Management Agency of Sijunjung Regency. The results of the F test found that work conflict and work discipline have a significant effect together on the work performance of ASN in the Regional Disaster Management Agency of Sijunjung Regency. The coefficient of determination value on the work performance of ASN in the Regional Disaster Management Agency of Sijunjung Regency is shown by the Adjusted R Square value of 0.662. This means that the contribution of work conflicts and the work environment to the work performance of ASN at the Sijunjung Regency Regional Disaster Management Agency is 66.2%, while the remainder is explained by other variables.